Psychological Distress and Dyadic Coping in the Context of Marital Satisfaction of Indonesian Search and Rescue (SAR) Rescuers: A Mixed-Method Study: [Tekanan Psikologis dan Dyadic Coping Dalam Konteks Kepuasan Pernikahan Search and Rescue (SAR) Rescuer di Indonesia: Studi Mixed-Method] - Khrisnanda, Faradita; Theresia Indira Shanti (Faculty of Psychology, Universitas Surabaya, 2022)
Marital satisfaction is an important resource that will determine the quality of life and personal well-being, as well as help maintain work performance in the context of Search and Rescue (SAR) rescuer profession. However, the risks associated with this profession put Search and Rescue (SAR) rescuers at risk of experiencing psychological distress that could hinder their marital satisfaction. In addition to psychological distress factors, efforts by Search and Rescue (SAR) rescuers in involving their sposes through dyadic coping were found to be associated with marital satisfaction. Using the mixed-method explanatory sequential method approach, this study aims to determine the role of psychological distress and social support on marital satisfaction of Search and Rescue (SAR) rescuers. Quantitative data collection involved Search and Rescue (SAR) rescuers in their first 10 years of marriage (n = 33). Qualitative data collection involved two Search and Rescue (SAR) rescuers with marital satisfaction in the high and low category, as well as dyadic coping in the high and low category. Results of quantitative analysis show that it is psychological distress, not dyadic coping, that significantly predict the decrease in marital satisfaction. Results of qualitative analysis show that psychological distress from the profession leads to symptoms of psychological distress in the form of emotional exhaustion, withdrawal behavior, and indifferent behavior, which has an impact on negative interactions, conflict triggers, and lack of quality time with spouses. Search and Rescue (SAR) rescuer who conduct dyadic coping (discussing with each other, providing opinions or points of view, and listening with empathy) leads to feelings of satisfaction in marriage, namely through feelings of togetherness and trust. Kepuasan pernikahan adalah sumber daya penting yang akan menentukan kualitas hidup dan kesejahteraan diri, serta membantu mempertahankan performa kerja pada konteks profesi Search and Rescue (SAR) rescuer. Namun, risiko yang berkaitan dengan profesi tersebut menempatkan Search and Rescue (SAR) rescuer untuk memiliki kerentanan mengalami tekanan psikologis yang dapat menghambat kepuasan pernikahannya. Selain faktor tekanan psikologis, upaya Search and Rescue (SAR) rescuer untuk melibatkan pasangan melalui dyadic coping ditemukan turut berhubungan dengan kepuasan pernikahan. Melalui metode mixed-method dengan pendekatan explanatory sequential design, studi ini bertujuan untuk mengetahui peranan tekanan psikologis dan dukungan sosial pada kepuasan pernikahan Search and Rescue (SAR) rescuer. Pengambilan data kuantitatif melibatkan Search and Rescue (SAR) rescuer dengan rentang usia pernikahan dalam 10 tahun pertama (n = 33). Pengambilan data kualitatif melibatkan dua individu Search and Rescue (SAR) rescuer dengan kepuasan pernikahan berkategori tinggi dan rendah, serta dyadic coping berkategori tinggi dan rendah. Hasil analisa kuantitatif menunjukkan bahwa bukan dyadic coping yang memprediksi penurunan kepuasan pernikahan secara signifikan, namun tekanan psikologis. Hasil analisa kualitatif menunjukkan bahwa tekanan psikologis yang bersumber dari profesi tersebut mengarah pada gejala tekanan psikologis berupa kelelahan emosional, perilaku menarik diri, dan perilaku acuh yang berdampak pada interaksi yang cenderung negatif, pemicuan konflik, dan minimnya waktu berkualitas dengan pasangan. Search and Rescue (SAR) rescuer yang melakukan dyadic coping (saling berdiskusi, memberikan pendapat atau sudut pandang, dan mendengarkan dengan empati) mengarah pada perasaan puas pada pernikahan, yakni melalui perasaan kebersamaan dan rasa percaya.